Electrical Resistivity Structure of Eyjafjallajökull Volcanic System based on Electromagnetic Data - Esteban Pineda 1989- (2018)
The use of Electromagnetic (EM) methods to investigate the electrical resistivity structure of volcanic systems has increased in recent times. Resistivity is most sensitive to fluid distribution and hydrothermal alteration as compared to other geophysical methods. The application of EM methods has been limited, for the most part, to geothermal exploration. In this study, two common EM methods, Magnetotellurics (MT) and Transient Electromagnetics (TEM), are used to map the subsurface resistivity distribution around the volcanic system of Eyjafjallajökull in southwest Iceland. Data were acquired over the course of three campaigns in 2011, 2014 and 2016. The campaign of 2011 was carried out jointly by Iceland GeoSurvey (ISOR) and Dublin Institute of Advanced Studies (DIAS), collecting 26 MT and 25 TEM sounding data. In the 2014 and 2016 campaigns, data from 5 MT stations were collected by students at the University of Iceland together with their supervisor from ISOR. Here all the data have been processed and 1D jointly inverted, and the results presented as resistivity cross-sections, depth slices and phase tensor maps. From the 1D inversion models, a shallow conductor located between 1-3 km depth and a deep-seated conductor located between 9-20 km depth have been found. The shallow conductor is seen across most of the investigated area. It is interpreted to be basalts containing hydrothermal alteration minerals in the form of smectites. The deep-seated conductor is mostly constrained to the northeastern part and is a feature that has been identified across most of Iceland in previous MT studies. However, its nature is poorly understood and presently debated. The phase tensor analysis favors a 1D Earth model for short periods (<10 s) and deviates to a 3D Earth model for long periods (>10 s). Induction arrows infer a more pronounced conductive structure beneath Eyjafjallajökull at shallow depth. Furthermore, a well-defined geoelectrical strike in the N75oE direction is identified for long periods. This might ...